The Hidden Welfare State : Tax Expenditures and Social Policy in the United States - Howard, Christopher (Book collections on Project MUSE., 2001)
Despite costing hundreds of billions of dollars and subsidizing everything from homeownership and child care to health insurance, tax expenditures (commonly known as tax loopholes) have received little attention from those who study American government. This oversight has contributed to an incomplete and misleading portrait of U.S. social policy. Here Christopher Howard analyzes the "hidden" welfare state created by such programs as tax deductions for home mortgage interest and employer-provided retirement pensions, the Earned Income Tax Credit, and the Targeted Jobs Tax Credit. Basing his wor.